Analysis of Farmers' Perceptions of the Profile of Agricultural Extension Workers in Padang Lawas District - Fauziah Marhanah Pohan; Mhd. Buhari Sibuea; Martial, Tri (ITScience (Information Technology and Science), 2024)
This study aims to analyze farmers' perceptions of agricultural extension profiles in Padang Lawas Regency.Farmers' perceptions are an important aspect that can influence the effectiveness of agricultural extension and the application of new technologies in agricultural practices. This research uses purposive sampling method with special considerations so that it is feasible to be used as a sample. The number of samples used in this study was 9 people. The variables analyzed include perceptions, the nature of the extension agent, the skills possessed by the extension agent, changes in farming. The results showed that farmers' perceptions of the profile of agricultural extension workers in Huristak sub-district were in the good category, with an average score of 713 with a percentage of 72.02%. Where the highest score was obtained by the sample extension officer Mr. Fahmi Saputra Harahap with a total score of 814 with a percentage of 82.22% where the highest score was in the aspect of farmer assessment of the nature of the extension officer with a total score of 357.8 with a percentage of 72.12% and categorized as good, and the lowest score was in the aspect of changes in farming with a total score of 128.8 with a percentage of 71.55% but still in the good category.